Barriers in performing physical assessment among nursing students: An integrative review - Jestoni D. Maniago; Evelyn E. Feliciano; Adelina M. Santos; Cyrelle L. Agunod; Cris S. Adolfo; Brian A. Vasquez; Abdulrhman Albougami; Joseph U. Almazan (Elsevier, 2021)
Objectives: This study aimed to identify barriers in performing physical assessments among nursing students through integrative review study. Methods: The literature were searched in Medline, CINAHL, ScienceDirect, Web of Science, ProQuest, and Taylor & Francis Online using the descriptors barrier, physical assessment, nursing student et al. Only English-language and peer-reviewed journal articles were included, and there were no year restrictions. Results: Twelve articles were selected for review. Two aspects were extracted: the barriers included personal challenges, challenges related to nursing education, challenges related to clinical practice; establishing competency-based education learning as a method to reduce physical assessment barriers. Student competencies and experiences were influenced by various factors that collectively hindered their successful performance of physical assessments. Conclusions: The review findings provide valuable insights into the complex issues involved in the performance of physical assessments and guidance for improvement in practice. A collaborative effort should be made to address the issues often faced by nursing students in performing routine physical assessments. Also, more constructive and competency-based teaching methods should be integrated into academic and clinical settings.